One-year readmission and Emergency department presentation after an epilepsy admission in people with intellectual disability: a registry-linkage study - Liao, Peiwen; Reppermund, Simone; Vajdic, Claire; Trollor, Julian N; Srasuebkul, Preeyaporn (International Journal of Population Data Science, 2019)
Background with rationale Although hospital admissions for epilepsy are common in people with intellectual disability (ID), little is known about the quality of inpatient care and outcomes after admission. To fill this gap, this project examines readmission, an important indicator for the quality of hospital care, and emergency department (ED) presentation after epilepsy admissions in people with ID compared to those without ID. Main Aim To examine whether people with ID have a higher risk of all-cause readmissions and ED presentations after discharge from the index admission (i.e. first admission within the study period) for epilepsy than people without ID. Methods In this retrospective data-linkage study, several linked administrative health datasets including but not restricted to hospital admissions, emergency department presentations, disability services and mental health ambulatory care are used to define the cohort, exposure and outcome. The cohort includes patients with and without ID who were admitted to hospital for epilepsy between 2002 and 2014 in New South Wales, Australia. The readmission rates and ED presentations within 28 days, 2-3 months, 4-6 months, and 7-12 months respectively will be compared between patients with and without ID. The effect of a diagnosis of ID on the risk of readmission and ED presentation within a year following the separation from the index admission will be estimated by Poisson regression. Results and conclusions The demographics and comorbidity profile of participants at the index epilepsy admission will be presented. Readmission and ED presentation rates within each chunk of follow-up will be calculated by the status of ID and the incidence rate ratio will be provided to estimate the impact of ID on these outcomes. Findings will provide insight into how patients with ID and epilepsy fare in hospital care and help to guide future management of epilepsy in people with ID.